IMPLEMENTASI PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS TENAGA KESEHATAN PADA RSUD dr. SAYIDIMAN MAGETAN - Wahna Widhianingrum; Premi Wahyu Widyaningrum; Ranti Kurniasih (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Abstract should The purpose of this study was to determine whether there is an influence of the application of occupational safety and health to the productivity of health staff at RSUD dr. Sayidiman Magetan. The data used in this study were obtained from a questionnaire (primary) and several observations and direct interviews with health staff at RSUD dr. Sayidiman Magetan. The analysis technique used is multiple regression analysis using the hypothesis test, namely the F test and the T test. This research will later be used as one of the scientific developments in the field of management, especially in the field of human resources. From this study it can be concluded based on statistical tests that overall occupational safety and health variables (simultaneous-F tests) have a positive effect on the productivity variables of health workers.